Genetic regulatory networks of soybean seed size, oil and protein contents - Duan, Zongbiao; Li, Qing; Wang, Hong; He, Xuemei; Zhang, Min (Frontiers in Plant Science, 2023)
Seed size is one of the most important agronomic traits determining soybean yield, a major oilseed crop that supplies plant oil and protein for daily human life. It can be described from three dimensions: length (diameter parallel to the hilum), width (diameter from the hilum to the back of the seed), and thickness (diameter vertical to the hilum). The amount of seed storage directly determines seed size. In general, oil and protein make up almost 60% of the total storage of soybean seed. Therefore, there is usually a strong correlation between the amount of oil and protein and seed size. In other words, increasing seed size not only helps improve soybean yield but also probably improves seed quality. This review summarized the progress in the regulatory mechanisms controlling soybean seed size, oil and protein contents in recent decades, and presented the challenges and prospects for developing high-yield soybean cultivars with high oil or protein content. In the end, we hope this review will contribute to the improvement of soybean yield and quality in the future breeding process.